ASSOCIATION OF EATING HABITS AND COOKING METHODS WITH BREAST TUMORS AMONG CHILDBEARING AGED URBAN WOMEN IN INDONESIA: A CROSS-SECTIONAL STUDY - Rathi Paramastri; Imaviana Cahyani; Khairizka Citra Palupi; Adi Kurniawan; Leffiyanti Handi; Mertien Sa’pang (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2023)
ABSTRACTBackground: breast tumors is the single most commonly detected benign or malignant tumors among women and has now become a global health burden.Objective: This study aimed to determine the associations of eating habits and cooking methods with a breast tumor in childbearing-aged Indonesian urban women.Materials and Methods: This was a cross-sectional study using a community survey of research of non-communicable disease 2016 database from the ministry of health of Indonesia. In total,28558 women, aged 25 – 49 years old were retrieved from the database. Eating habits and cooking methods were measured using a validated food frequency questionnaire. A forward logistic regression analysis was used to examine the association of eating habits and cooking methods with the risk of breast tumors.Results: Higher education level was positively associated with the incidence of breast tumors (OR = 1.10, 95%CI: 1.01-1.20, p = 0.026). Seafood (OR = 0.88, 95% CI: 0.80-0.96, p = 0.006) and fast foods (OR = 1.10, 95% CI: 1.00-1.20, p = 0.049) were associated with the incidence of breast tumor among urban women. Roasted/smoked cooking method was positively associated with risk of breast tumor (OR = 1.27, 95%CI: 1.01 – 1.61, p = 0.043).Conclusion: Our study is the first community-based study in Indonesia investigating the association of eating habits and cooking methods with the incidence of breast tumors among childbearing-aged urban women. High intake of seafood was associated with a lower risk of breast tumors, while fast foods and roasted/smoked cooking method belief to have a detrimental effect on a breast tumor. Prospective studies are needed to confirm the present study findings.Keywords : eating habits, cooking methods, breast tumor, urban women